Influence of a Probiotic Containing Lactobacillus fermentum on the Laying Performance and Egg Quality of Japanese Quails - Kalsum , U.; Soetanto, H.; Achmanu; Sjofjan, O. (International Journal of Poultry Science, 2012)
The objective of this study was to investigate the potential of Lactobacillus fermentum, isolated from the intestine of Japanese quails (Coturnix japonica), as a probiotic product. The influence of this probiotics preparation on the laying performance and egg quality of quails was evaluated in a 28-day experiment. A fully randomized design was used with four experimental treatments, namely standard feed, standard feed with antibiotic, standard feed with 5.27 x 108 cells/ml L. fermentum and standard feed with 2.35 x 109 cells/ml L. fermentum. The results showed that L. fermentum supplementation did not influence (p>0.05) egg quality parameters (haugh unit, % egg albumen, % egg yolk and egg shell thickness) and egg weight, but significantly improved (p